A Novel Orientation Recursive Algorithm Aiming at Catastrophe Signals in MWD - Yang, Jinxian; Chao, Lijun (IEEE transactions on industrial electronics (1982), 2020)
In this article, we investigate the problem of optimal orientation of the drilling tool which is subject to catastrophe signals in measurement while drilling (MWD). The proposed algorithm is characterized by the signal extraction and filtering of catastrophe signals. First, the reference frames and the orientation of the MWD surveying system, including a triaxial gyroscope, a triaxial accelerometer, and a triaxial magnetometer, are described. Subsequently, the orientation-dependent components, i.e., the Earth's gravity and geomagnetic vector, are decoupled from the measurement signals based on the Coriolis transfer equation. Finally, a new type of filter dealing with the catastrophe signals, i.e., Catastrophe filter, is designed. Performance has been evaluated by the simulations and actual drilling tests and also benchmarked against another most-favored method. The results indicate the proposed algorithm has achieved a higher level of accuracy in MWD.